Enhancing School Image Through Strategic Digital Marketing: A SOSTAC Based Approach - Endah Windiastuti; Kharisma Adi Tama (Universitas Negeri Jakarta, 2026)
This study examines the digital marketing strategy implemented by SMP Budi Mulia Dua Yogyakarta to strengthen its school image, which had previously been perceived as “expensive” and “exclusive.” Using a qualitative approach, data were collected through interviews, observations, and documentation, and were analyzed using the Miles and Huberman interactive model. The findings show that the school systematically applies the SOSTAC framework (Situation Analysis, Objectives, Strategy, Tactics, Action, and Control) in managing its digital presence. Various platforms, including Instagram, TikTok, YouTube, and the official website, are utilized to share information and highlight academic and non-academic programs. Consistent and visually appealing content successfully enhances public awareness and reshapes perceptions of the school. The digital strategy effectively strengthens the four dimensions of brand equity according to Keller: brand identity, brand meaning, brand response, and brand resonance. Despite limited human resources, the school’s commitment to continuous content production has positively influenced its overall public image.